2021
DOI: 10.1177/2378023120985648
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality, Social Comparison, and Happiness in the United States

Abstract: Using social comparison theory, I investigate the relation between experienced happiness and income inequality. In the analysis, I study happiness effects of the individual-level within-gender-ethnicity comparison-based Gini index conditional on a state’s overall inequality, using a linked set of the March 2013 Current Population Survey and the 2013 American Time Use Survey data while controlling major potential confounders. The findings suggest that individuals who are positioned to conduct both upward and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 75 publications
1
14
0
1
Order By: Relevance
“…From the moderator approach, researchers had proposed two groups of moderators, national differences and personal factors, to help reconcile the perplexed association between income and SWB. National differences include socioeconomic contexts such as popularity density, income inequality, and social mobility [ 15 , 16 ], cultural values such as individualism versus collectivism, uncertainty avoidance, and masculinity versus femininity [ 17 , 18 , 19 ], and political factors [ 20 , 21 ], among others. In terms of personal factors, researchers have found that the direction and strength of the link between income and SWB differ by gender [ 22 ], age [ 23 ], personality [ 24 ], and social class memberships [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the moderator approach, researchers had proposed two groups of moderators, national differences and personal factors, to help reconcile the perplexed association between income and SWB. National differences include socioeconomic contexts such as popularity density, income inequality, and social mobility [ 15 , 16 ], cultural values such as individualism versus collectivism, uncertainty avoidance, and masculinity versus femininity [ 17 , 18 , 19 ], and political factors [ 20 , 21 ], among others. In terms of personal factors, researchers have found that the direction and strength of the link between income and SWB differ by gender [ 22 ], age [ 23 ], personality [ 24 ], and social class memberships [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of urbanization, part of the rural population was directly transformed into urban population, and their living land was classified as urban land [ 10 , 11 , 12 , 13 ]. In addition, some areas have been urbanized by migrating rural population to urban areas, which has also reduced the number of permanent residents in rural areas [ 14 , 15 , 16 ]. On the other hand, urban areas have more employment opportunities than rural areas, and wages in urban areas are higher than in rural areas [ 17 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…If this is correct, it is important to acknowledge that not all young people experience this phenomenon in the same way. Before research can effectively explore the relationship between expectations and happiness, investigations must begin at the individual level to consider the implications of everyday experiences (Liao, 2021).…”
Section: Young People and Happinessmentioning
confidence: 99%